The importance of micrometeorological variations for photosynthesis and transpiration in a boreal coniferous forest - G. Schurgers (Biogeosciences, 2015)
Plant canopies affect the canopy micrometeorology, and thereby alter canopy exchange processes. For the simulation of these exchange processes on a regional or global scale, large-scale vegetation models often assume homogeneous environmental conditions within the canopy. In this study, we address the importance of vertical variations in light, temperature, CO2 concentration and humidity within the canopy for fluxes of photosynthesis and transpiration of a boreal coniferous forest in central Sweden. A leaf-level photosynthesis-stomatal conductance model was used for aggregating these processes to canopy level while applying the within-canopy distributions of these driving variables. The simulation model showed good agreement with eddy covariance-derived gross primary production (GPP) estimates on daily and annual timescales, and showed a reasonable agreement between transpiration and observed H2O fluxes, where discrepancies are largely attributable to a lack of forest floor evaporation in the model. Simulations in which vertical heterogeneity was artificially suppressed revealed that the vertical distribution of light is the driver of vertical heterogeneity. Despite large differences between above-canopy and within-canopy humidity, and despite large gradients in CO2 concentration during early morning hours after nights with stable conditions, neither humidity nor CO2 played an important role for vertical heterogeneity of photosynthesis and transpiration.